Noncovalent Li···H Interaction in the Synthesis of peri-Disubstituted Naphthalene Proton Sponges - Antonov, Alexander S.; Yakubenko, Artyom A. (Synthesis, 2020)
Noncovalent Li···H interaction was utilised as a tool for the second lithiation of 4-lithio-1,8-bis(dimethylamino)naphthalene with n-BuLi in the presence of TMEDA in hexane. Metallation proceeds with 100% selectivity in the second peri-position and with up to 90% yield. A series of 4,5-disubstituted derivatives of 1,8-bis(dimethylamino)naphthalene has been prepared in good to excellent yield after quenching the reaction mass with different electrophiles.
Keywords: agostic interaction; metalation; proton sponge; lithium; naphthalene